Exosomes as Drug Carriers in Anti-Cancer Therapy - Chen, Lan; Wang, Li; Zhu, Lingling; Xu, Zihan; Liu, Yanyang; Li, Zhixi; Zhou, Jin; Luo, Feng (Frontiers in Cell and Developmental Biology, 2022)
Over the years, there has been a high demand for developing new safe and effective drug carriers for cancer therapy. Emerging studies have indicated that exosomes can serve as potent therapeutic carriers since they offer low immunogenicity, high stability, innate and acquired targetability, and the stimulation of anti-cancer immune responses. Yet, the development of exosome-based drug delivery systems remains challenging due to their heterogeneity, low yield, and limited drug loading efficiency. Herein, we summarized the current application of exosomes derived from different cells as drug carriers in anti-cancer therapy in vitro and in vivo. We also discussed the challenges and prospects of exosome-based drug delivery systems in cancer therapy.